The Acquisition of Technological Capability: Towards an Analytical Model - Zulkieflimansyah, Zulkieflimansyah (UI Scholars Hub, 2002)
In neo-classical framework, technology is defined in a static way. It is a product, a package, that is produced by one set of firms or other institutions and consumed or used by another. And as firms all operate on a given production function, their technological tasks is merely to choose whichever technology is most appropriate to their needs. The firms can shift their position on the production function effortlessly in response to change in economic circumstances. The evolutionary approach, on the other hand, views technology in a more dynamic way. The successful adoption of technology involves more than merely the purchase of machinery and the learning of operating procedures. This means that firms cannot shift effortless along the production function, nor operate any particular technique immediately at optimal efficiency.